(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The article determines that under the influence of political, socio-economic, and educational trends, there is a decrease in children’s physical activity. In this regard, there is a need to restore the vitality and physical strength that students lose during their studies, emotional stress, stress, and round-the-clock gadget and computer use. This, in turn, contributes to the active search for new methods and means of restoring physical and psycho-emotional states. The purpose of the article is to clarify the essence of the concept of "sports animation" based on the analysis of research by scientists and to formulate its classification for today. Based on the analysis of theoretical material, the article analyzes the concept of "animation", defines "sports animation" as a type of recreational activity in the field of physical culture, considers the types of "sports animation" as a type of animation activity aimed at forming a healthy lifestyle, involving participants in active, creative, creative, interpersonal interaction, which achieves the greatest health-improving effect with the help of sports physical education. It involves physical and psycho-emotional recovery, involvement in creative and social activity, and enjoyment of it. . On the basis of theoretical analysis and systematization of the works of scientists, the author defines his own classification of types of sports animation, which includes: outdoor games; recreational sports games; sports mass events; physical culture and health activities. Thus, sports animation can be considered a type of mass recreational physical culture, and its types are aimed at meeting human needs for maintaining and improving health, promoting a healthy lifestyle, encouraging physical education and sports, recreation, and national and patriotic education.